HUBUNGAN PENGETAHUAN TENTANG POLUSI UDARA DAN SIKAP IBU TERHADAP KEJADIAN ISPA PADA BALITA DI WILAYAH KERJA PUSKESMAS PEKANBARU KOTA - Poetra, Ricky Perdana; Yulis, Dian Meiliani; Kartadarma, Supriyatni; Sari, Novi Maya; Situmeang, Lamria (Ensiklopedia of Journal, 2024)
The prevalence of ARI in toddlers has decreased when compared to the 2013 riskesda, the prevalence of acute respiratory infections decreased from 25.0% in 2013 to 9.3% in 2018. Based on case report data, during January - August 2021 in Pekanbaru City, 9,169 cases of visits by toddlers with difficulty breathing were reported, 7 toddlers died from ARI and 3,147 were estimated to have severe pneumonia. The purpose of the study was to determine the relationship between knowledge about air pollution and maternal attitudes towards the incidence of ispa in toddlers in the Pekanbaru City Health Center working area. This study used a type of quantitative research with a cross sectional design. The instrument in this study used a questionnaire. Data analysis was univariate and bivariate using chi square test. The results of the study were that there was a relationship between knowledge about air pollution with the incidence of ARI of toddlers in the work area of the city Pekanbaru health center with a p value of 0.004 and there was a relationship between maternal attitudes about air pollution with the incidence of ARI of toddlers in the work area of the city Pekanbaru health center with a p value of 0.034.  It is recommended for mothers to increase knowledge by always following counseling about health, especially nutritional status in children, as well as for health workers to further improve counseling for families, health counseling, and improve health services. to the Puskesmas to determine the right strategy in providing health services.Keywords: Toddler, ISPA, Maternal Knowledge, Maternal Attitude